Hexavalent chromium disrupts mitosis by stabilizing microtubules in Lens culinaris root tip cells. Issue 2 (23rd June 2012) - Eleftheriou, Eleftherios P.; Adamakis, Ioannis‐Dimosthenis S.; Fatsiou, Maria; Panteris, Emmanuel
<x xml:space="preserve">Abstract</x> Hexavalent chromium [Cr(VI)] is an accumulating environmental pollutant due to anthropogenic activities, toxic for humans, animals and plants. Therefore, the effects of Cr(VI) on dividing root cells of lentil (Lens culinaris) were investigated by tubulin immunofluorescence and DNA staining. In Cr(VI)‐treated roots, cell divisions were perturbed, the chromosomes formed irregular aggregations, multinucleate cells were produced and tubulin clusters were entrapped within the nuclei. All cell cycle‐specific microtubule (MT) arrays were affected, indicating a stabilizing effect of Cr(VI) on the MTs of L. culinaris. Besides, a time‐ and concentration‐dependent gradual increase of acetylated α‐tubulin, an indicator of MT stabilization, was observed in Cr(VI)‐treated roots by both immunofluorescence and western blotting. Evidence is also provided that reactive oxygen species (ROS) caused by Cr(VI), determined with the specific marker dichlorofluorescein, may be responsible for MT stabilization. Combined treatments with Cr(VI) and oryzalin revealed that Cr(VI) overcomes the depolymerizing ability of oryzalin, as it does experimentally introduced hydrogen peroxide, further supporting its stabilizing effect. In conclusion, it is suggested that the mitotic aberrations caused by Cr(VI) in L. culinaris root cells may be the result of MT stabilization rather than depolymerization, which consequently disturbs MT dynamics and their related functions.